Impact of CYP2C9*3 polymorphisms and clinical variables on the valproic acid levels of Iraqi patients suffering from grand mal epilepsy - Makki Al-Hindy, Hayder Abdul-Amir; Jaafar Mousa, Mazin; Obayes Hashim, Hayder; Nasser Hussien, Tabark; Ahmed Mohammed, Malak (Pharmakeftiki, 2025)
Generalized tonic-clonic seizures form the key characteristic of severe epilepsy which neurologists call “grand mal” epilepsy. Targeting both epilepsy management and seizure control, valproic acid (VA) stands as one of the prevalent antiepileptic medications. CYP2C9*3 is a mutation of the cytochrome P450 2C9 gene that encrypts an enzyme in charge of VA metabolism. Variants of CYP2C9*3 substantially influence drug metabolism, affecting therapeutic outcomes and toxicity. This study has evaluated how VA metabolism depends on CYP2C9*3 pleomorphisms while investigating clinical factors that impact drug levels in epilepsy. We have conducted a prospective cross-sectional study on 28 epileptic patients at the Merjan Medical City in Babylon (Iraq), from September 2024 to December 2024. VA levels were higher in epileptic patients bearing the C/C mutant genotype compared to those of patients with A/A or A/C genotypes. The dose of VA depends mainly on the age and the body mass index (BMI) of a patient. Those bearing mutant C/C genotypes displayed significantly higher VA concentrations than those with A/A or A/C variants. Moreover, age and BMI were recognized as crucial elements of VA dosing, highlighting the necessity of personalized styles for adjusting treatment efficacy while decreasing side effects. The study has shown that CYP2C9*3 affects VA levels among grand mal epileptic patients, since patients expressing the C/C variant displayed higher blood levels of the drug. Future research should consider that optimum therapeutic outcomes require treatment approaches that account for the personal genetic constitution and clinical features.